Development of a fast and low-cost qPCR assay for diagnosis of acute gas pharyngitis - Kolukırık, Mustafa; Yılmaz, Mesut; İnce, Orhan; Ketre, Canan; Tosun İstanbullu, Ayşe; İnce Kasapgil, Bahar (BioMed Central Ltd., 2016)
Background: Group A streptococci (GAS) are the most common bacterial cause of acute pharyngitis and account for 15-30 % of cases of acute pharyngitis in children and 5-10 % of cases in adults. In this study, a real-time quantitative PCR (qPCR) based GAS detection assay in pharyngeal swab specimens was developed. Methods: The qPCR assay was compared with the gold standard bacterial culture and a rapid antigen detection test (RADT) to evaluate its clinical performance in 687 patients. The analytical sensitivity of the assay was 240 cfu/swab. Forty-five different potential cross-reacting organisms did not react with the test. Four different laboratories for the reproducibility studies were in 100 % (60/60) agreement for the contrived GAS positive and negative swab samples. Results: The relative sensitivities of the RADT and the qPCR test were 55.9 and 100 %; and the relative specificities were 100 and 96.3 %, respectively. Duration of the total assay for 24 samples including pre-analytical processing and analysis changed between 42 and 55 min depending on the type of qPCR instrument used. A simple DNA extraction method and a low qPCR volume made the developed assay an economical alternative for the GAS detection. Conclusion: We showed that the developed qPCR test is rapid, cheap, sensitive and specific and therefore can be used to replace both antigen detection and culture for diagnosis of acute GAS pharyngitis.
Keywords: Acute Pharyngitis; Group A Streptococci; QPCR; Rapid Antigen Detection Test